Risk management in the Malaysian Public Private Partnership projects - Usman Ahmad,; Yusnidah Ibrahim,; Arpah Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The Malaysian government has been implementing Public Private Partnership (PPP) program since 1980s for infrastructure development. The literature shows that quite a number of PPP projects failed to achieve their objectives due to lack of risk management. Nonetheless, literature on risk management process for different type of PPP projects is lacking. In addition, the literature does not provide the robust measurements to study PPP risk management as a variable in the field of risk management. Therefore, this study aims to describe risk management practices for PPP projects in Malaysia. To facilitate the empirical research, the current study develops a set of items for describing PPP risk management processes by employing exploratory sequential research design. The findings show existence of some forms of risk management in PPP projects where the agreement and design concept form a vital role in risk management.